2005
DOI: 10.4269/ajtmh.2005.73.371
|View full text |Cite
|
Sign up to set email alerts
|

Status of Forest Onchocerciasis in the Lower Cross River Basin, Nigeria: Entomologic Profile After Five Years of Ivermectin Intervention

Abstract: In the Lower Cross River basin in Nigeria, no pre-control entomologic profile of Onchocerca volvulus infection in the local Simulium damnosum population was available prior to the initiation of an ivermectin control program in 1995. A longitudinal entomologic study was therefore carried out over a 12-month period (January-December 2001) at the Agbokim waterfalls and Afi River, which are breeding sites of S. damnosum in the river basin. A total of 9,287 adult S. damnosum were caught on human bait; 9,048 (97.43%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 28 publications
6
28
2
Order By: Relevance
“…In the previous studies, Kutin et al (2004), Opara et al (2005) and Usip et al (2006) have found the similar results.…”
Section: Discussionsupporting
confidence: 73%
“…In the previous studies, Kutin et al (2004), Opara et al (2005) and Usip et al (2006) have found the similar results.…”
Section: Discussionsupporting
confidence: 73%
“…Cattle rearing and bee farming are largely practiced. A detailed description of the study site and area is documented elsewhere (Opara et al 2005;Ibanga 2004). …”
Section: Study Sitementioning
confidence: 99%
“…Some Simulium species can transmit Onchocerca volvulus, causative parasites of river blindness (onchocerciasis) in Africa (WHO, 1995). Clinical manifestations of onchocerciasis include itching and disfiguring of skin, nodules on bony areas, serious eye lesions, and blindness; all of these are considered both public health problems and socioeconomic hazards (Opara et al, 2005;Youssefi et al, 2008). In countries like India, even despite evidence of O. volvulus not being reported so far, black flies still bite and crawl on the skin of individuals and livestock (Malhotra et al, 1986).…”
Section: Introductionmentioning
confidence: 99%